Association between obstructive sleep apnea and resistant hypertension: systematic review and meta-analysis - Ahmed, Abass Mahamoud; Nur, Salman Mohamud; Xiaochen, Yuan (Frontiers in Medicine, 2023)
Obstructive sleep apnea syndrome (OSAS) is a chronic disorder characterized by recurring episode obstruction and collapse of upper airways during sleep, leading to hypoxia and sleep disruption. OSAS is commonly associated with an increased prevalence of hypertension. The underlying mechanism in OSA with hypertension is related to intermittent hypoxia. This hypoxia induces endothelial dysfunction, overactivity of sympathetic effects, oxidative stress, and systemic inflammation. Hypoxemia triggers the sympathetic process's overactivity, leading to the development of resistant hypertension in OSA. Thus, we hypothesize to evaluate the association between resistant hypertension and OSA. Methods: The PubMed, cliniicaltrail.gov, CINAHL, Google Scholar, Cochrane Library, and Science direct database were searched from 2000 to January 2022 for studies demonstrating the association between resistant hypertension and OSA. The eligible articles underwent quality appraisal, meta-analysis, and heterogeneity assessment. Results: This study comprises seven studies, including 2,541 patients range 20-70 years. The pooled analysis of six studies demonstrated that OSAS patients with a history of increased age, gender, obesity, and smoking status are at increased risk for resistant hypertension (OR: 4.16 [3.07, 5.64], I2:0%) than the non-OSAS. Similarly, the pooled effect demonstrated that patients with OSAS were at increased risk of resistant hypertension (OR: 3.34 [2.44, 4.58]; I2:0%) than non-OSAS patients when all associated risk factors were adjusted using multivariate analysis. Conclusion This study concludes that OSAS patients with or without related risk factors demonstrated increased risk for resistant hypertension.